RANCANG BANGUN MESIN FILAMENT PET UNTUK 3D PRINTER - Adifa Septira, Alma Hamni; -, Wachidin (Jurnal TEDC, 2024)
Currently, among the public, the use of plastic bottles, which are a type of Polyethylene Terephalate (PET) plastic, has become a culture for consumption as a container for packaged drinks. However, the use of this type of plastic bottle has a very bad impact on the environment. PET is a type of plastic that is easily reshaped, so one step that can be taken to utilize this waste is to make it into 3D Printer filament. To process PET plastic bottle waste into 3D printer filament, a PET filament machine for 3D printers is needed. In the process of designing and building this machine, you are required to carry out research first using various methods such as observation, literature study and Internet media. This PET filament machine for 3D Printers processes PET plastic bottle waste which has been cut into bottle strips like ribbons according to the specified size and then heated using a heater to a temperature of 270°C through the nozzle hole to make a 1.65mm filament and the filament is rolled. automatically with a motor speed of 2.5 Rpm.